Potensi Madu dan Ekstrak Ampas Teh Sebagai Penghambat Tirosinase Untuk Bahan Aktif Kosmetika Pemutih - Sumarlin, La Ode; Ernita, Nur; Hajar, Hajar (ALCHEMY:Journal of Chemistry, 2023)
One way to lighten skin tone is to inhibit the formation of melanin through the inhibition of the tyrosinase enzyme. Bleach acts as an inhibitor of melanin production and is known as a competitive tyrosinase inhibitor. In this study, the potential for teabag and honey dregs will be analyzed singly and in the form of a mixture. The method used is an anti-tyrosinase test using L-DOPA as a substrate. The results of the analysis showed that the tea extract samples were almost all positive test compounds (Flavonoids, Alkaloids, Tannins, Saponins, Steroids) except for Quinones and Triterpenoids. Honey for the positive sample was only for saponin compounds, while those for other compounds were negative. Tea extract has the potential to inhibit the tyrosinase enzyme, because it contains flavonoid compounds, tannins and steroids. Tests for inhibition of the tyrosinase enzyme in honey and tea and a mixture of the two have IC50 values 1000 g/ml, so the inhibitory activity is very weak. However, research has shown that tea bag dregs and honey have the potential to be used as active ingredients in whitening cosmetics.